NFV-COIN: Unleashing The Power of In-Network Computing with Virtualization Technologies - Venâncio, Giovanni (2022)
Network Functions Virtualization (NFV) allows the implementation in software of middleboxes traditionally available as specialized hardware. Network services can be implemented as SFCs (Service Function Chains) based onvirtualization technologies that run on commodity hardware. Although most virtualized functions have classic middlebox functionalities (e.g. firewalls or intrusion detectors) NFV technology can be used to leverage the networkto provide novel types of services to end-users. Actually, NFV can be very convenient to deploy traditional enduser services in the network, in the paradigm that has been called Computing In the Network (COIN). This articlediscusses the requirements to deploy COIN services using NFV technologies, which we call NFV-COIN. We alsopresent case studies and an NFV-COIN architecture that is compliant with the NFV-MANO reference model.